BENEFITSEGMENTATION: Case of a National Bank's Customers in Indonesia - Ahnad Yunianto; Catur Sugiyanto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
Fierce competition in Indonesian banking industry had forced banks to get closer to their customers in order to maintain their customer base. However, considering the banks limited resources and the market competition, raised question on which customers they should focus to serve. Benefit segmentation as one of the concept of market segmentation, provides a clear picture of which segment or type of customers the bank should focus. Undertaken in a national bank, this research was aimed to identify benefits desired by the customer in financial service; segments for the bank based on those benefits; and to identify whether there is a relationship between customers' demographics and their desired benefits. Factor analysis with principal component method was used to extract 29 banking attributes to a set of factors that capable to capture the main features of the responses. Cluster analysis was then applied to the dataset to identify whether a bundle of benefit might be sought by a specific customer segment. The last, chi-square test was applied to identify whether there is any correlation between the cluster and the demographic variables. Five factors (main benefits) sought by the customers were found, namely: safety-convenience; relational; bank's features; cost; and promotional incentives. Based on those factors, the customers could be classified into four segments, service-oriented (38.41%), rate sensitive (16.85%), incentive seekers (13.30%), and safety-convenience (31.44%). A significant correlation between demographic characteristics (gender, age, education, income, monthly spending, occupation, and number of children) and desired customer benefits were found. Therefore, those demographic characteristics could be used to develop the customers' profiles.